PERCEPTION OF COMMUNITIES AROUND BETWEEN AGROWISM: Cas Study in Karangsari Village, Sukorejo Subdistrict, Blitar City - Ria Yunitasari (JOSAR (Journal of Students Academic Research), 2018)
The purpose of this study was to determine the perceptions of the community on the presence of starfruit agro-tourism areas and perceptions of each starfruit agro-tourism variable. This research was conducted in Blitar City, which was located in Karangsari Sub-District, Sukorejo Sub-District, Blitar City in April 2018. Based on the results of the study, the community's response to starfruit agro-tourism with perceptions strongly agreed was 62.5% and those who agreed agreed 37.5% and those with a neutral perception , disagree and strongly disagree. Whereas the responses from each variable for the economic aspects that perceived strongly agree 45.5%, agree 48.25%, neutral 6.25% and those who perceive disagree and strongly disagree does not exist. For environmental aspects, the perception is strongly agree 49.75%, agree 41.75%, neutral 8.5% and those who perceive disagree and strongly disagree does not exist. For the security aspect, those who perceive strongly agree 52%, agree 43.5%, neutral 4.5% and those who perceive disagree and strongly disagree do not exist and for cultural aspects who perceive strongly agree 44.25%, agree 46.75% , neutral 9% and those who perceive disagree and strongly disagree does not exist.